Fungsi Partai Politik dalam Memberikan Pendidikan Politik Bagi Masyarakat - Masriyani Masriyani; Herma Yanti (Wajah Hukum, 2019)
Democracy is a government by the people, which is interpreted as the most basic. as stipulated in article 28 of the 1945 Constitution, which states that: "freedom of association and assembly, issuing thoughts by word and mouth and so forth is stipulated by law." One of the media to apply article 28 can be channeled through political parties. is a research in normative juridical specifications, about the functions of political parties on political education for the public and its juridical consequences, which are normatively regulated in Law No. 2 of 2011. The issues discussed are how to regulate the functions of political parties related to political education to the community. The results of the study show that in Law No. 2 of 2011 it has been regulated that the function of political parties is to carry out political education in the community. Where further regulation of the Act is the establishment of Government Regulation number 1 of 2018 in which it provides arrangements relating to priority funding assistance for the implementation of such education. From the existence of financial assistance both from the APBN / APBD received by political parties, it will result in juridical consequences for accountability to the Supreme Audit Agency.